P-Element Homing Is Facilitated by engrailed Polycomb-Group Response Elements in Drosophila melanogaster - Cheng, Yuzhong; Kwon, Deborah Y.; Arai, Allison L.; Mucci, Diane; Kassis, Judith A. (PLOS ONE, 2012)
P-element vectors are commonly used to make transgenic Drosophila and generally insert in the genome in a nonselective manner. However, when specific fragments of regulatory DNA from a few Drosophila genes are incorporated into P-transposons, they cause the vectors to be inserted near the gene from which the DNA fragment was derived. This is called P-element homing. We mapped the minimal DNA fragment that could mediate homing to the engrailed/invected region of the genome. A 1.6 kb fragment of engrailed regulatory DNA that contains two Polycomb-group response elements (PREs) was sufficient for homing. We made flies that contain a 1.5kb deletion of engrailed DNA (enΔ1.5) in situ, including the PREs and the majority of the fragment that mediates homing. Remarkably, homing still occurs onto the enΔ1. 5 chromosome. In addition to homing to en, P[en] inserts near Polycomb group target genes at an increased frequency compared to P[EPgy2], a vector used to generate 18,214 insertions for the Drosophila gene disruption project. We suggest that homing is mediated by interactions between multiple proteins bound to the homing fragment and proteins bound to multiple areas of the engrailed/invected chromatin domain. Chromatin structure may also play a role in homing.